1993
DOI: 10.1002/1097-4679(199305)49:3<358::aid-jclp2270490309>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of the MCMI-I and MCMI-II with psychiatric outpatients

Abstract: Research indicates that the Millon Clinical Multiaxial Inventory (MCMI-I) lacks diagnostic accuracy when compared to clinically generated DSM-111-R diagnoses. This shortcoming is most evident for the identification of psychotic disorders. The MCMI-I1 was designed to reflect more accurately the DSM-111-R diagnostic formulation, but its diagnostic efficacy has yet to be determined with clinical samples. In the present investigation, two consecutive samples of psychiatric patients who were attending an outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…One of diagnostic objective, true-false tools is Millon Clinical Multiaxial Inventory (MCMI) which is based on Millon Diagnostic accuracy of the MCMI-I is less than DSM-III-R diagnoses, especially for psychotic disorders. The MCMI-I and MCMI-II minimized the frequency of psychotic disorders and overrated the frequency of personality disorders (PD) and nonpsychotic disorders in psychiatric outpatients (Inch, & Crossley, 1993). Libb, Murray, and Alarcon (1992) indicated that MCMI-II is tied to DSM-III-R diagnoses, and is a diagnostic tool and provides useful information related to diagnostic categories in the most of psychiatric situations.…”
Section: Introductionmentioning
confidence: 99%
“…One of diagnostic objective, true-false tools is Millon Clinical Multiaxial Inventory (MCMI) which is based on Millon Diagnostic accuracy of the MCMI-I is less than DSM-III-R diagnoses, especially for psychotic disorders. The MCMI-I and MCMI-II minimized the frequency of psychotic disorders and overrated the frequency of personality disorders (PD) and nonpsychotic disorders in psychiatric outpatients (Inch, & Crossley, 1993). Libb, Murray, and Alarcon (1992) indicated that MCMI-II is tied to DSM-III-R diagnoses, and is a diagnostic tool and provides useful information related to diagnostic categories in the most of psychiatric situations.…”
Section: Introductionmentioning
confidence: 99%
“…Note. Four additional studies(Curtis & Cowell, 1993;Divac-Jovanovic, Svrakic, & Lecic-Tosevski, 1993;Inch & Crossley, 1993;Piersma, 1987) of the MCMI and personality disorders are not included because insufficient data were available in publications and attempts to secure additional data from authors were unsuccessful. CL, Clinician diagnoses; BSI, Borderline Syndrome Index; D IB-R, Diagnostic Interview for Borderlines-Revised; MMPI-PD, Morey et al's personality scales for the MMPI; NPI, Narcissistic Personality Inventory; PCL-R, Psychopathy Checklist-Revised; PDE, Personality Disorder Examination; PDI, Personality Disorder Inventory; PDQ, Personality Disorder Questionnaire; PIQ, Personality Interview Questions; PSCL, Personality Symptom Checklist; RNPI,…”
mentioning
confidence: 99%
“…Most of this literature has focused on comparisons of later versions of the MCMI to earlier editions (Inch & Crossley, 1993;Piersma, 1989aPiersma, , 1989bStreiner & Miller, 1989), its ability to detect deviant item responses (Bagby, Gillis, & Rogers, 1991;Retzlaff, Sheehan, & Fiel, 1991), the diagnostic congruence of the MCMI to clinician ratings (Chick, Sheaffer, & Goggin, 1993;Inch & Crossley, 1993;Soldz, Budman, Demby, & Merry, 1993), the operating characteristics of the MCMI (Gibertini, Brandenburg, & Retzlaff, 1986;Miller et al, 1993;Piersma, 1991;Retzlaff, 1996), or its specific psychometric properties (Choca, Stanley, & VanDenburg, 1992;Gibertini & Retzlaff, 1988;Piersma, 1989b;Retzlaff & Gibertini, 1987;. Relative to this body of research, fewer studies have investigated the possibility of summarizing the MCMI scales for more parsimonious interpretation (e.g., with techniques such as factor analysis).…”
mentioning
confidence: 99%